(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study was to investigate the effect of different irrigants (EDTA, MTAD, CHX) on the sealing ability of new Bioceramic root canal sealer. Material and methods: A total of sixty extracted human single-rooted premolar teeth were used. After instrumentation, teeth were randomly divided into three main groups (n=20) according to the type of final irrigants used. In group (A) 17% EDTA was used. Group (B) irrigants was MTAD. In group (C) irrigant was 2% CHX. Each main group further subdivided into two subgroup (n=10) according to the type of sealer used. Subgroup (1) canals obturated with Bioceramic sealer. In subgroup (2) canals obturated with AH plus sealer. After incubation period for one week the roots were placed in 2% methylene blue dye and kept in incubator for 48 hours then the roots were cleared, dye penetration measured by stereomicroscopic. Results: statistical significant difference was found between groups (p<0.001). In subgroup (1) BC sealer & CHX showed the lowest mean of leakage in comparing to other type of irrigants with highly significance difference with BC sealer & EDTA. In subgroup (2) AH Plus & EDTA showed the lowest mean of apical leakage. A highly significance differences was found between subgroup (1) and subgroup (2) for all type of irrigants. (p<0.001).Conclusion: when Bioceramic sealer is used in obturation of root canal system, it is better to use it in combination with CHX irrigant to improve the apical seal.